Distribution and Habitat Characteristics of the Green Tree Frog (Rhacophorus reinwardtii Schlegel, 1840) in East Java. - Mochammad Yordan Adi Pratama; Fatchur Rohman; Agus Dharmawan; Vivi Novianti; Sri Rahayu Lestar (Fakultas Biologi Universitas Gadjah Mada, 2023)
The IUCN Red List classifies the green tree frog (Rhacophorus reinwardtii) as a frog that is Least Concern. One study that has never been carried out in Indonesia concerns the spatial distribution of the green tree frog based on Geographic Information System (GIS) applications and the habitat characteristics in East Java. It is vital to map the spatial distribution of the green tree frog in East Java and identify its habitat characteristics because the amphibian diversity surveys that have been conducted so far are the only ones available. This study is quantitative descriptive in design, with studies of pertinent literature as supporting sources. Cruising and the Visual Encounter Survey (VES) method are the techniques employed. A Geographic Information System (GIS) application is utilized in the computational method to create a spatial distribution analysis by gathering information on the locations of interactions with green tree frogs. Based on findings from studies conducted in the Bromo Tengger Semeru National Park Area (TNBTS), the Tancak Kembar Waterfall Area in Bondowoso Regency, and the Ironggolo Waterfall Area in Kediri Regency, there are 16 green tree frog meeting points recorded on the iNaturalist application for the Our Reptile Amphibian Observation Movement (GO-ARK) project and 3 points from the outcomes of field observations. In East Java, environmental factors such as altitude, slope, rainfall, NDVI, land cover, and proximity to rivers have a significant impact on how green tree frogs are distributed spatially. Although green tree frogs in East Java frequently forsake water bodies and choose to live in high-level plant types, they also frequently occupy a variety of water bodies. The green tree frogs discovered at the research location are categorized as favoring continuous habitats with boundaries for colony development.